Evaluation of the mixtures ammonium phosphate/magnesium nitrate and palladium nitrate/magnesium nitrate as modifiers for simultaneous determination of Cd, Cr, Ni and Pb in mineral water by GFAAS - Amorim Filho, Volnei R. [UNESP]; Fernandes, Kelly G. [UNESP]; De Moraes, Mercedes [UNESP]; Gomes Neto, José Anchieta [UNESP] (FapUNIFESP (SciELO), 2004)
A method is described for the simultaneous determination of Cd, Cr, Ni and Pb in mineral water samples by graphite furnace atomic absorption spectrometry with a transversely heated graphite atomizer (THGA) and a longitudinal Zeeman-effect background correction system. The electrothermal behavior of analytes during pyrolysis and atomization steps was studied without modifier, in presence of 5 μg Pd and 3 μg Mg(NO3)2 and in presence of 50 μg NH4H2PO4 and 3 μg Mg(NO3)2. A volume of 20 μL of a 0.028 mol L -1 HNO3 solution containing 50 μg L-1 Ni and Pb, 10 μg L-1 Cr and 5 μg L-1 Cd was dispensed into the graphite tube at 20°C. The mixture palladium/magnesium was selected as the optimum modifier. The pyrolysis and atomization temperatures were fixed at 1000°C and 2300°C, respectively. The characteristic masses were calculated as 2.2 pg Cd, 10 pg Cr, 42 pg Ni and 66 pg Pb and the lifetime of the graphite tube was around 600 firings. Limits of detection based on integrated absorbance were 0.02 μg L-1Cd, 0.94 μg L-1 Cr, 0.45 μg L-1 Ni and 0.75 μg L-1 Pb, which exceeded the requirements of Brazilian Food Regulation that establish the maximum permissible level for Cd, Cr, Ni and Pb at 3 μg L-1, 50 μg L-1, 20 μg L-1 and 10 μg L-1, respectively. The recoveries of Cd, Cr, Ni and Pb added to mineral water samples varied within the 93-108%, 96-104%, 87-101% and 98-108% ranges, respectively. Results of analysis of standard reference materials (National Institute of Standards and Technology: 1640-Trace Elements in Natural Water; 1643d-Trace Elements in Water) were in agreement with certified values at the 95% confidence level.
Keywords: GFAAS; Inorganic trace elements; Mineral water; Simultaneous determination; ammonium derivative; cadmium; chromium; lead; magnesium derivative; mineral water; nickel; nitric acid derivative; palladium; phosphate; atomic absorption spectrometry; electrochemistry; evaluation; mathematical computing; nebulization; pyrolysis; temperature measurement; thermal analysis